2019
DOI: 10.1093/ajh/hpz104
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour vs. Spot Urinary Sodium and Potassium Measurements in Adult Hypertensive Patients: A Cohort Validation Study

Abstract: BACKGROUND Sodium intake is correlated with the development of hypertension. Guyton’s principals suggest that the 24-hour urinary sodium excretion reflects sodium ingestion over the same period. 24-hour urine collections are arduous to collect, so many centers use spot urinary measurements instead. We compared spot to matched 24-hour urinary electrolyte measurements. METHODS We examined 419 hypertensive patients from the UCL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The most critical limitation, sodium intake, as estimated using urinary sodium excretion on the basis of single-spot urine sampling, may have contributed to large variations in the data. Some studies reported that urinary sodium-to-creatinine ratios derived from spot urine sampling correlated weakly with those derived from 24-h urine collection 55 . Multiple reports suggest sodium intake calculated using the Tanaka formula is biased with overestimation at lower levels and underestimation at higher levels [55][56][57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most critical limitation, sodium intake, as estimated using urinary sodium excretion on the basis of single-spot urine sampling, may have contributed to large variations in the data. Some studies reported that urinary sodium-to-creatinine ratios derived from spot urine sampling correlated weakly with those derived from 24-h urine collection 55 . Multiple reports suggest sodium intake calculated using the Tanaka formula is biased with overestimation at lower levels and underestimation at higher levels [55][56][57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that urinary sodium-to-creatinine ratios derived from spot urine sampling correlated weakly with those derived from 24-h urine collection 55 . Multiple reports suggest sodium intake calculated using the Tanaka formula is biased with overestimation at lower levels and underestimation at higher levels [55][56][57][58][59] . A method such as 24-h urine collection may have provided a more accurate evaluation of sodium intake.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline mean salt consumption of participants in this study was 8.94g per day, but with the CM-DASH diet, the mean salt intake of participants was reduced by approximately 4g per day. As the golden criteria to determine the intake of sodium, 24-hour urine electrolyte electrolytes has been widely used in scientific research [18] .Our results shows that after the intervention of CM-DASH diet, the 24-hour urine Na + of the intervention group and the control group both decreased significantly, which indicated that CM-DASH diet had a marked effect on reducing the sodium intake of the participants. Studies have shown that high dietary sodium intake can lead to high BP by inhibiting the activity of Na + -K + -ATPase pumps in cell membrane [19] , damaging vascular endothelial function [20] and activating RAAS (Renin-Angiotension-Aldosterone System) [21] .…”
Section: Discussionmentioning
confidence: 61%
“…In a cross-sectional study, spot urine sodium ratio was compared to 24-hour collection content. 24-hour and spot sodium concentrations correlated moderately (r = 0.46) and gave a very poor understanding of the natriuresis occurring over the same 24-hour period, without relating to nutrition or potassium [45]. Correlation between Na þ /K þ ratios measured in spot urine vs. 24-hour collection was found to be statistically significant in another trial, yet the authors did not address intake or response to change in diet [46].…”
Section: Fig 3 Change In Mean Urine Electrolytes Ratio [Namentioning
confidence: 99%